SUMBER FLUKTUASIKURS: TEORI DAN STUDI EMPIRIS - Florentius Nugro Hardianto (Center for Economic Studies Universitas Katolik Parahyangan, 2010)
Stabilization of domestic currency exchange rate towards international currency especially US Dollar is important part of macro economy policy. This policy always is strived for a government in good certain time period in short-run or long-run. Based on discussion in this paper, there are some factors that can be source the happening of rate fluctuation. Theoretical, financial market variables and riel macroeconomic variables are the important factor that can influence rate fluctuation. Some of the variables are interest rate, money supply, financial liberalization, domestic and international price, productivity, government expenditure, and employment. Meanwhile, the result of empirical study by Daly (2006) indicated that riel macroeconomic variables were obvious more important role in influencing rate fluctuation movement at amount of country.